BENTUK CAMPUR KODE DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Febriyani febri (Buana Bastra, 2023)
This article discusses the phenomenon of code mixing in the novel Laskar Pelangi by Andrea Hirata. Code mixing is the use of language or style of language that mixes two or more different language codes. The purpose of this study is to analyze and explain the form of code mixing used in the novel and to identify the reasons for using code mixing by the author.